Peningkatan Kreativitas Siswa SMK Melalui Pengenalan Dasar Digital Marketing Berbasis AI - Siregar, Dodi; Rahayu, Sri; Saputra, Imam; Sari, Dian Purnama; Sari, Vina Winda (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2026)
This community service program aimed to enhance the creativity of vocational high school students through the introduction of basic artificial intelligence (AI)-based digital marketing. The implementation method included literature review, partner needs assessment, and hands-on training involving 20 participants. The results revealed a significant improvement in participants’ understanding, where initially 80% were categorized as low, but after the training, 60% were categorized as good. Satisfaction responses also indicated that most participants felt satisfied or highly satisfied with the materials and delivery methods. This program demonstrates that introducing AI-based digital marketing can serve as an effective approach to foster 21st-century skills among vocational school students. However, the limitation of this activity lies in its short duration, which restricted the coverage of advanced materials, yet it provides a strong foundation for future community service initiatives.